How Do Brand Awareness and Inovation Influence Purchasing Decisions - Anam, Chairul; Rahayu, Betty; Nurhayati, Wina (Yayasan Pendidikan Belajar Berdikari, 2023)
In order to improve consumer purchase decisions, this study attempts to investigate if brand awareness can moderate promotional activities, product quality, and product innovation. The study was carried out at PT Dharma Satya Nusantara, a new wood product craftsman company. Causal associative method in quantitative research. Purposive sampling was used in the questionnaire-based data gathering process, which had 142 respondents. analysis of data with the Smart PLS 3.0 software. The study's findings demonstrate that while brand awareness is a moderating variable, there is insufficient data to support its ability to regulate marketing campaigns, product innovation, and quality in order to influence customer purchase decisions. Nonetheless, it has been demonstrated that brand awareness can predict consumer purchasing decisions more accurately than other factors. By strengthening brand recognition as a predictor, boosting promotional activities, and enhancing product quality, the study's findings aid in efforts to enhance purchasing decisions